The Ameliorating Effect of Oral Paquinimod Administration against Imiquimod Induced Psoriasis-like Inflammation in Mice - Khaleel, Raghad Abdulsalam (Iraqi Journal of Pharmaceutical Sciences, 2023)
Psoriasis is a chronic, inflammatory condition that primarily affects the skin, hair, and joints and is associated with significant humanistic and economic consequences. Psoriasis was induced in mice in this work using an imiquimod 5% cream, an immune response modifier that can cause psoriasis-like skin inflammation when given orally. Paquinimod is prepared as a suspension and has been orally given to mice before imiquimod application. The current study found that paquinimod suspension reduced psoriasis area and severity index, spleen index, skin thickness ,TNF-α,IL-23,IL17 level and gene expression of TNF-α,Nf-KB,IL-1B,IL-17in the (Paquinimod suspension+imiquimod) group substantially more than the (vehicle suspension+imiquimod) groups.